Comment on “Worldwide evidence of a unimodal relationship between productivity and plant species richness” - Tredennick, Andrew T.; Adler, Peter B.; Grace, James B.; Harpole, W. Stanley; Borer, Elizabeth T.; Seabloom, Eric William; Anderson, T. Michael; Bakker, Jonathan D.; Biederman, Lori A.; Brown, Cynthia S.; Buckley, Yvonne M.; Chu, Chengjin; et al. (American Association for the Advancement of Science, 2021)
Fraser et al. (Reports, 17 July 2015, p. 302) report a unimodal relationship between productivity and species richness at regional and global scales, which they contrast with the results of Adler et al. (Reports, 23 September 2011, p. 1750). However, both data sets, when analyzed correctly, show clearly and consistently that productivity is a poor predictor of local species richness.